2020
DOI: 10.1016/j.ihj.2020.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of stress hyperglycemia on myocardial salvage in patients with ST-Elevation myocardial infarction: Cardiac magnetic resonance study

Abstract: Cardiovascular complications in ST-segment–elevation myocardial infarction survivors remain substantial despite advances in the management of STEMI. We aimed to determine effect of AH on the area at risk (AAR), final infarct size (FIS), and salvage index (SI) in STEMI patients using cardiac magnetic resonance (CMR). 43 successfully reperfused STEMI patients were recruited. CMR was utilized to estimate AAR and FIS, SI was calculated: SI = AAR- FIS/AAR. AH showed significant positive correlations to FIS ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Neuroendocrine disorders can also lead to insulin resistance in the body [10][11][12]. Hematoma compression can lead to hypothalamuspituitary-adrenal axis injury and reduce the biological uptake and utilization of glucose in peripheral tissues [13,14]. In contrast, hyperglycemic state can affect brain tissue energy metabolism, leading to acidosis due to lactic acid accumulation and can induce oxidative stress, which aggravates neuronal cell damage and is detrimental to the prognosis of patients with cerebral hemorrhage [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Neuroendocrine disorders can also lead to insulin resistance in the body [10][11][12]. Hematoma compression can lead to hypothalamuspituitary-adrenal axis injury and reduce the biological uptake and utilization of glucose in peripheral tissues [13,14]. In contrast, hyperglycemic state can affect brain tissue energy metabolism, leading to acidosis due to lactic acid accumulation and can induce oxidative stress, which aggravates neuronal cell damage and is detrimental to the prognosis of patients with cerebral hemorrhage [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of patients with diabetes in the two groups was statistically different. Hyperglycemia is strongly associated with a poor prognosis after reperfusion treatment in STEMI patients [31,32] . This may be, in part, due to the general in ammation that characterizes diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Free radicals aggravate oxidation, produce a large number of lipid peroxides in the blood and adhere to the vessel wall, making the blood vessel cavity thinner, the pipe wall rough, the elasticity weaker and the blood vessel brittle, thus increasing the incidence of cardiovascular events. It is found that the level of blood glucose is positively correlated with the size of myocardial infarction area [8]. The higher the blood glucose level is, the higher the infarct size is.…”
Section: Damage To Heartmentioning
confidence: 93%